Calorie restriction increases lipopolysaccharide-induced neuropeptide Y immunolabeling and reduces microglial cell area in the arcuate hypothalamic nucleus. (29th January 2015) - Radler, M.E.; Wright, B.J.; Walker, F.R.; Hale, M.W.; Kent, S.
Highlights: Calorie restriction increased neuropeptide Y-immunolabeling in the arcuate nucleus. Calorie restriction reduced microglia area following lipopolysaccharide. Neuropeptide Y was negatively correlated with body temperature. Body temperature was positively correlated with microglia area. Abstract: Calorie restriction (CR) increases longevity and elicits many health promoting benefits including delaying immunosenescence and reducing the incidence of age-related diseases. Although the mechanisms underlying the health-enhancing effects of CR are not known, a likely contributing factor is alterations in immune system functioning. CR suppresses lipopolysaccharide (LPS)-induced release of pro-inflammatory cytokines, blocks LPS-induced fever, and shifts hypothalamic signaling pathways to an anti-inflammatory bias. Furthermore, we have recently shown that CR attenuates LPS-stimulated microglial activation in the hypothalamic arcuate nucleus (ARC), a brain region containing neurons that synthesize neuropeptide Y (NPY), an orexigenic neuropeptide that is upregulated by a CR diet and has anti-inflammatory properties. To determine if increased NPY expression in the ARC following CR was associated with changes in microglial activation, a set of brain sections from mice that were exposed to 50% CR or ad libitum feeding for 28 days before being injected with LPS were immunostained for NPY. The density of NPY-immunolabeling was assessed across the rostrocaudal extent of the ARC and hypothalamic paraventricular nucleus (PVN). An adjacent set of sections were immunostained for ionized calcium-binding adapter molecule-1 (Iba1) and immunostained microglia in the ARC were digitally reconstructed to investigate the effects of CR on microglial morphology. We demonstrated that exposure to CR increased NPY expression in the ARC, but not the PVN. Digital reconstruction of microglia revealed that LPS increased Iba1 intensity in ad libitum fed mice but had no effect on Iba1 intensity in CR mice. CR also decreased the size of ARC microglial cells following LPS. Correlational analyses revealed strong associations between NPY and body temperature, and body temperature and microglia area. Together these results suggest that CR-induced changes in NPY are not directly involved in the suppression of LPS-induced microglial activation, however, NPY may indirectly affect microglial morphology through changes in body temperature.